Ozone nanobubble treatment in freshwater effectively reduced pathogenic fish bacteria and is safe for Nile tilapia (Oreochromis niloticus) - Chayuda Jhunkeaw (2022)
High concentrations of certain pathogenic bacteria in water usually results in outbreaks of bacterial diseases in farmed fish. Here, we explore the potential application of an emerging nanobubble technology in freshwater aquaculture, specifically aimed to reduce the concentrations of pathogenic fish bacteria in freshwater, and assess whether nanobubbles are safe for Nile tilapia (Oreochromis niloticus). An ozone nanobubble (NB-O3) treatment protocol was established, based on examination of nanobubble size, concentration, disinfection property, and impact on fish health. A 10-min treatment with NB-O3 in 50 L water generated approximately 2–3 × 107 bubbles/mL, with the majority of bubbles being less than 130 nm in diameter and an ozone level of 834 ± 22 mV oxidation-reduction potential (ORP). A single treatment with water spiked with either Streptococcus agalactiae or Aeromonas veronii effectively reduced the bacterial load by 26–48 fold or 96.11–97.92%. This same protocol was repeated three times. The result was a 22,058 to 109,978 fold reduction in bacteria or 99.93–99.99% decrease. In comparison, bacterial concentrations in the control tanks remained unchanged during the experiments. In Nile tilapia-cultured water with the presence of organic matter (e.g. mucus, feces, bacterial flora, feed, etc.), the disinfection property of NB-O3 was reduced; however, we still observe a reduction of 59.63%, 87.25%, and 99.29% after the first, second, and third consecutive treatments, respectively. To evaluate the safety of NB-O3 on fish, juvenile Nile tilapia were exposed to NB-O3 treatment for 10 min. No mortality was observed during the treatment or 48 h post treatment. Gill histology examination revealed that a single NB-O3 treatment caused no alteration in cell morphology. However, damage in the gill filaments, such as blood congestion, aggregates of basal cells at the secondary lamellae or loss of the secondary lamella was noticed in the fish receiving two or three consecutive exposures within the same day. Results of the experiments conducted in this study suggest that NB-O3 technology is promising for reducing pathogenic bacteria in aquaculture systems and may be useful at reducing the risk of bacterial disease outbreaks in farmed fish.